Matharpacady-07.jpg - Mumbai Archive Project Team (Jio Institute, 2024)
The metal balustrade on the balcony at Mi Casa, 20A Matharpacady, features portraits of Queen Victoria, clearly installed in the late 19th century during her rule. The name Mi Casa means ‘My Home’ in Spanish. Like Mi Casa, most of the 40-odd surviving heritage bungalows in Matharpacady are painted in bright colours, a feature of Indo-Portuguese architecture, seen in neighbourhoods like Fontainhas in Panjim, Goa.